MENELAAH PEMIKIRAN JASSER AUDA DALAM MEMAHAMI MAQASID SYARIAH - Ari Murti (DAS Institute, 2021)
The formulation of legal concepts regarding Islamic law is an exciting theme to study. Islamic law derived from the Qur'an and Hadith was born from the process of interpretation and ijtihad of the scholars whose results may vary. This book presents multidisciplinary research on Islamic legal theory. According to Jasser Auda, the United Nations Development Program (UNDP) states that the Human Development Index (HDI) of countries with Muslim populations is still low. Low literacy, education, political and economic participation, empowerment of women, decent standards and quality of life, and level of justice. To develop an analytical theory of Islamic law, maqasid sharia results from research by offering new ideas as a philosophy and basic methodology for current Islamic legal theory. Through two approaches, namely the first, the time and historical approach, Jasser Auda made a historical map of the development of Islamic legal thought starting from the era of traditional Islam, Modern Islam, to Postmodern Islam. Then the second approach, namely through a systems approach which is a kind of anti-modernity-style philosophical approach by bringing the basic concepts commonly used are Cognitive Nature from Islamic Law, looking at the problem as a Wholeness, interrelationships between values (Interrelated Hierarchy), involving various dimensions (Multidimensionality), and prioritizing and prioritizing the subject (purposefulness). The resulting research is in the validation of several ijtihad methodologies that are realized in maqasid sharia. Practically, this concept produces Islamic rules that are conducive to justice, moral values, expected life, and the development of humanity.